Analysis of the Legal Treatment of Reverse Logistics for Waste Electrical and Electronic Equipment in Brazil in Comparison to the Systems Adopted by Portugal and Spain - Souza, Ana Beatriz do Amaral; Serotini , André (Scientific Journal ANAP, 2025)
Objective: This study critically analyzes the legal treatment of reverse logistics for waste electrical and electronic equipment (WEEE) in Brazil, comparing it to the regulatory models implemented in Portugal and Spain. It aims to identify gaps in Brazilian legislation and propose improvements based on European experiences, contributing to the enhancement of waste management in the country.Methodology: The methodology is based on a qualitative approach, including a bibliographic review and documentary analysis of national and international regulations on reverse logistics. The comparative research allows for an examination of different regulatory models, assessing their applicability in the Brazilian context and their potential to strengthen the circular economy.Originality: The originality of the study lies in the need to deepen the understanding of the effectiveness of the Brazilian National Solid Waste Policy (PNRS) and to identify successful foreign practices that could be adapted to the national scenario. The research fills a theoretical gap by comparatively evaluating extended producer responsibility and mechanisms of oversight and incentives, aspects that have been little explored in Brazilian literature.Results: The main findings indicate that, despite regulatory advancements, the implementation of WEEE reverse logistics in Brazil still faces structural and operational challenges. In contrast, Portugal and Spain have more consolidated systems, with effective oversight mechanisms and economic incentives that encourage greater participation from the productive sector and civil society.Theoretical/Methodological Contributions: Theoretical and methodological contributions include an in-depth analysis of comparative environmental legislation, providing a foundation for future research on improving reverse logistics in Brazil. Additionally, the study suggests methodological guidelines for assessing the effectiveness of environmental public policies, contributing to empirical studies on electronic waste governance.Social and Environmental Contributions: The study’s social and environmental contributions are significant, as proper WEEE management reduces negative environmental impacts such as soil and water contamination by heavy metals. Furthermore, strengthening the circular economy and integrating waste pickers into the reverse logistics system can generate social and economic benefits, promoting sustainable development.
Keywords: Reverse logistics; Waste electrical and electronic equipment; Circular economy; Environmental law; Public policies